Taḥlīl al-Akhṭāʾ an-Naḥwiyah fī al-ʿAdad wa Al-Maʿdūd li al-Faṣl aṡ-Ṡāliṡ bi Maʿhad Dārissalām Gontor Li al-Banāt: Analisis Kesalahan Nahwu dalam al-ʿAdad wa Al-Maʿdūd Kelas 3 di Pondok Modern Darussalam Gontor Putri - Abdul Hafidz bin Zaid; Nurlina Siregar; Lubis, Rahmat Hidayat; Ifa Rodifah Nur (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2024)
Analysis of nahwu errors is the linguistic analysis of errors in terms of nahwu by defining, describing, and explanation of those errors. Grammar errors occur due to ignorance of nahwu rules. One of the nahwu rules used by the students at Gontor for Girls is the rule of the ‘adad and the ma’dūd. The students understand numbers in Arabic but find it challenging to apply the correct rule of the 'adad and the ma’dūd due to a lack of understanding of that rule. This research aims to identify the forms of errors and analyze nahwu errors in the ‘adad and the ma’dūd for the third grade at Darussalām Islamic Institution Gontor for Girls for the academic year 2022-2023. In this research, the researcher uses qualitative research with a descriptive approach. The researcher uses the document method in collecting data taken from daily tests in the ‘adad and the ma’dūd to address the forms of nahwu errors in the ‘adad and the ma’dūd. The results of this research show that the forms of nahwu errors in the ‘adad and the ma’dūd for the third grade at Darussalām Islamic Institution Gontor for Girls for the academic year 2022-2023 consist of errors in tażkīr and ta’nīṡ, in iḍāfah, with tamyīz. As for the analysis of nahwu errors in the ‘adad and the ma’dūd for the third grade at Darussalām Islamic Institution Gontor for Girls for the academic year 2022-2023, after definition, description and explanation, there are some errors that occur 20 times in tażkīr and ta’nīṡ, 5 times in iḍāfah, and 9 times in tamyīz. To improve the quality of teaching the Arabic language to students, teachers should pay attention to the difficulties and problems faced by students in learning the Arabic language, especially in teaching the 'adad and the ma’dūd, and students should be given more exercises in the ‘adad and the ma’dūd. Keywords: ‘Adad and Ma’dūd, Errors Analysis, Nahwu